1997
DOI: 10.1089/hyb.1997.16.413
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Tolerability, and Preliminary Efficacy of Human Anti-Pseudomonas aeruginosaMonoclonal Antibodies in Pneumonia and Burn Infection Patients

Abstract: Human monoclonal antibody (hMAb) cocktail SM-17220 (also known as BT-570), a heterofunctional antibody mixture of 3 human IgM MAbs (HI-223, MH-4H7, and IN-2A8; ratio of 1:10:10) directed against Pseudomonas aeruginosa, were administered to patients with pneumonia or burn wounds (or both) to assess the pharmacokinetics, safety, antigenicity, and preliminary efficacy. Twenty mg of SM-17220 was IV infused over 60 min once daily on 3 consecutive days. Twenty patients (8 pneumonia, 4 burns, and 8 both) completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Our findings from the acute lung infection model in mice did not indicate enhanced macroscopic lung pathology in KBPA101-treated mice. In the past tolerability and pharmacokinetics of other MAb preparations of IgM isotype in humans has been documented in patients with pneumonia, bacteremia and burn wounds associated with P. aeruginosa infection (12,38). In both studies the preparations of antibodies were demonstrated to be safe and well tolerated with no evidence of acute complement consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings from the acute lung infection model in mice did not indicate enhanced macroscopic lung pathology in KBPA101-treated mice. In the past tolerability and pharmacokinetics of other MAb preparations of IgM isotype in humans has been documented in patients with pneumonia, bacteremia and burn wounds associated with P. aeruginosa infection (12,38). In both studies the preparations of antibodies were demonstrated to be safe and well tolerated with no evidence of acute complement consumption.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many at-tempts to generate human MAbs of different isotypes against various antigens of P. aeruginosa, such as LPS, alginate, or PcrV (reviewed by Doring and Pier [8]). Most of these MAbs demonstrated protection in animal models (18,25,30,39,41,47,48), and some were subsequently tested in clinical settings (12,27,38), but none of these MAbs have been licensed for routine use in humans thus far.…”
mentioning
confidence: 99%
“…A few investigators have tried to use epitopes in the more conserved core of the P. aeruginosa LPS as targets for protective antibodies (Harrison et al, 1997;Noguchi et al, 1991;Terashima et al, 1991;Yokota et al, 1990), but these have not yet shown any efficacy in clinical trials. Other investigators failed to find protective efficacy associated with LPS core epitopes (Hatano et al, 1995).…”
Section: Role Of P Aeruginosa Lps In Virulence and Immunity To Infecmentioning
confidence: 99%
“…[198][199][200] A human mAb cocktail of three IgM mAbs, each directed against P. aeruginosa O-polysaccharide, LPS core polysaccharide or flagellin type b, showed promising results in patients with pneumonia and/or burn wounds as far as safety, antigenicity and efficacy was concerened. 201 Using a more novel approach, transgenic mice with its immunoglobulin genes replaced with human immunoglobulin loci were used to generate a panel of O-polysaccharide-specific human IgG2 mAbs targeted against multiple P. aeruginosa serotypes. 202 The majority of these One of the limitation of Ad vector as vaccine carrier is that the anti-Ad immunity following the first immunization prevents the boosting of the immune response by repeat administration of the same Ad serotype.…”
Section: Passive Immunotherapymentioning
confidence: 99%